2013
DOI: 10.1038/ncomms3760
|View full text |Cite
|
Sign up to set email alerts
|

A cholinergic trigger drives learning-induced plasticity at hippocampal synapses

Abstract: Learning induces plastic changes in synapses. However, the regulatory molecules that orchestrate learning-induced synaptic changes are largely unknown. Although it is well established that cholinergic inputs from the medial septum modulate learning and memory, evidence for the cholinergic regulation of learning-induced synaptic plasticity is lacking. Here we find that the activation of muscarinic acetylcholine (ACh) receptors (mAChRs) mediates the contextual fear learning-driven strengthening of hippocampal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
178
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(191 citation statements)
references
References 43 publications
12
178
0
1
Order By: Relevance
“…The ripple-like firing may code experienced information, as selective suppression of hippocampal ripples impairs spatial memory in dorsal CA1 [28]. Moreover, we previously found that contextual learning requires the plasticity at excitatory/inhibitory synapses in CA1 [8,9]. Our results, together with the previous studies, we hypothesized that the excitatory/inhibitory synaptic plasticity creates the ripple-like events to process the experienced context by using the theta phase-locked processing system.…”
Section: Reviewsupporting
confidence: 64%
See 2 more Smart Citations
“…The ripple-like firing may code experienced information, as selective suppression of hippocampal ripples impairs spatial memory in dorsal CA1 [28]. Moreover, we previously found that contextual learning requires the plasticity at excitatory/inhibitory synapses in CA1 [8,9]. Our results, together with the previous studies, we hypothesized that the excitatory/inhibitory synaptic plasticity creates the ripple-like events to process the experienced context by using the theta phase-locked processing system.…”
Section: Reviewsupporting
confidence: 64%
“…A point with high appearance probability (around the mean level) indicates low self-entropy, while a point with very rare probability (a deviated point) indicates high self-entropy. Compared with untrained rats, the self-entropy per neuron was clearly increased in IA-trained rats but not in unpaired or walk-through rats [8]. This analysis suggests a learning-induced increase in the amount of information in CA1 neurons.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Moreover, several studies showed that hippocampal nAChR activation by nicotine and other nAChR agonists resulted in enhanced hippocampal LTP (Fujii and Sumikawa 2000;Welsby et al 2006Welsby et al , 2007Jia et al 2010); that is, strengthening of weak stimulation-induced short-term LTP (Fujii et al 1999;Matsuyama et al 2000;Matsuyama and Matsumoto 2003) as well as direct induction of LTP (He et al 2000;Matsuyama et al 2000;Matsuyama and Matsumoto 2003). Moreover, antagonism of nAChRs blocked learning-induced CA1 LTP (Mitsushima et al 2012). In addition to the effects of acute administration of nicotine and other direct nAChR agonists, hippocampal plasticity has been shown to be altered during nicotine withdrawal.…”
Section: Modulation Of Hippocampal Plasticity By Nicotinementioning
confidence: 99%
“…Moreover, mAChR activation can modulate the production or/and the release of neurotrophic factors in neurons, such as brain-derived neurotrophic factor (BDNF) and fibroblast growth factor-2 (FGF2), which in turn could mediate synaptic plasticity, axon outgrowth, and neurogenesis (Barathi et al 2009;Lindholm et al 1994;Mudo et al 1996;Navakkode and Korte 2012). Several of these effects involve mainly M1 receptor in adult hippocampus (Dennis et al 2016;Mitsushima et al 2013).…”
Section: Introductionmentioning
confidence: 99%